Ukraine towards the european digital market: the status and tools for implementing the european digital economy and society index - Semenchenko, Andrii; Oleksiuk, Liliia (Pressing Problems of Public Administration, 2022)
Ukraine’s entry into the European digital market as one of the priority directions of the state’s foreign policy actualizes the problem of introducing the global Digital Economy and Society Index (DESI), which is widely used in the EU, into the national statistical monitoring system. The article analyzes the readiness of the implementation of the DESI index in Ukraine. It has been proven that with the adoption of the laws of Ukraine “On electronic communications” and “On the National Commission carrying out state regulation in the spheres of electronic communications, radio frequency spectrum and the provision of postal services” a legal basis was created for the implementation of the DESI Index, which needs its further development in the direction of its detailing and concretization through the adoption of a set of by-laws. An organizational mechanism for the implementation of the DESI index is proposed, with the definition of a number of main subjects from state bodies and the definition of their role in the process of implementing this index, primarily the regulatory body and its tasks in the formation of the “connectivity” sub-index. The main problems of implementing the DESI Index in Ukraine are summarized and ways of solving them are proposed.